Indications and long‐term outcomes of preoperative inferior vena caval filters in 111 patients at high risk of pulmonary embolism undergoing major abdominal surgery. (29th June 2021) - Kostadinov, Danko; Tzivanakis, Alexios; Ubhayakar, Gaurang; Dixon, Shaheen; Helyar, Vincent; Dayal, Sanjeev Paul; Mohamed, Faheez; Cecil, Thomas Desmond; Moran, Brendan John
Abstract: Aims: Patients with abdominal cancer requiring major surgical intervention are at high risk of venous thromboembolic events (VTE), particularly pulmonary emboli (PE). A proportion of patients with cancer can present with, or have had, major VTEs prior to definitive surgical treatment. Preoperative percutaneous inferior venal caval filters (IVCF) may reduce the risk of PE. The aim of this study was to assess the indications, complications, retrieval rates, and long‐term outcome of IVCFs in patients undergoing major abdominal surgery. Methods: This was a retrospective analysis of a prospective IVCF database between 2007 and 2018 of all patients with IVCF insertion prior to major abdominal surgery. The indications for an IVCF, procedural complications and surgical interventions were recorded. Results: Overall, 111 patients had IVCF insertion. IVCF placement failed in one patient with gross abdominal disease. Indications for an IVCF were: prior PE in 65/111 (59%) and major vein thrombus in 42 (38%). Overall, 26/111 (23%) had the IVCF removed at a median of 91 days. In two patients IVCF removal failed. At follow‐up of the 85 patients who had the IVCF left in situ, six developed filter‐related thrombus and 13 a deep vein thrombosis (DVT). Four patients had a PE with an indwelling IVCF. Conclusion: Preoperative IVCF may reduce perioperative PE in patients at high risk of thrombosis undergoing major abdominal surgery where early anticoagulation is contraindicated. Long‐term follow‐up of retained IVCF suggests that major problems are infrequent, though further thrombosis may occur and long‐term anticoagulation may be needed.